Future theranostic strategies: emerging ovarian cancer biomarkers to bridge the gap between diagnosis and treatment - Rajapaksha, Weranga; Khetan, Riya; Johnson, Ian R. D.; Blencowe, Anton; Garg, Sanjay; Albrecht, Hugo; Gillam, Todd A. (Frontiers in Drug Delivery, 2024)
Ovarian cancers are a complex and heterogenic group of malignancies that are difficult to detect, diagnose and treat. Fortunately, considerable knowledge of ovarian cancer specific biomarkers has been generated, that is pertinent to the development of novel theranostic platforms by combining therapies and diagnostics. Genomic and proteomic data has been invaluable in providing critical biomolecular targets for ovarian cancer theranostic approaches. Yet, to date few platforms have developed into clinical application. Exploitation of the wealth of biomarker research that has been conducted offers viable targets as beacons for ovarian cancer detection, diagnosis, and therapeutic targeting. These markers can be used in theranostics, a treatment strategy that combines therapy and diagnostics and is common in nuclear medicine, where radionuclides are used for both diagnosis and treatment. The development of theranostics has taken substantial focus in recent years in the battle against ovarian cancer. Yet to date only one theranostic technology has emerged in clinical practice. However, given the wealth of ovarian cancer biomarkers we are poised to see the emergence of revolutionary disease treatment and monitoring outcomes through their incorporation into the development of eventual theranostic strategies. The future of ovarian cancer treatment is set to enable precise diagnosis, targeted treatment, and vigilant monitoring. This review aims to assess the status of ovarian cancer diagnostic tools and biomarkers in practice, clinical development, or pre-clinical development, highlighting newly emerging theranostic applications.